IMPLEMENTATION OF ARTICLE 3 LAW NUMBER 4 OF 2009 CONCERNING MINERAL AND COAL MINING IN THE GRANTING OF EXPLORATION MINING BUSINESS LICENSE - Anggalana; Dery Putra; Chandra Reformasi (Law Faculty of Universitas Bandar Lampung, 2021)
Indonesia is a country rich in natural resources. Therefore, the Government isexpected to be able to manage these natural resources with the aim of people's welfare in accordance with the mandate of the Constitution of the Republic of Indonesia 1945 as stipulated in Article 33 paragraph (3) which reads